Terapi birth ball berpengaruh terhadap lama kala II dan intensitas nyeri persalinan pada ibu bersalin primigravida di RB Kasih Ibu Yogyakarta - Tri Maryani; Dwiana Estiwidani (Jurnal Kesehatan Ibu dan Anak, 2016)
Background: Childbirth and birth is a physiological process that must be experienced by a mother. During the process, childbirth occurs a decrease in the head into the pelvic cavity and contractions that cause a painful sensation felt by the mother. Various attempts were made to reduce labor pain, both pharmacologically and non-pharmacology. The pharmacologic method can be performed between deep breaths and distractions with birth balls. Objective: To determine the effect of birth ball therapy on the duration of the second stage of labor and a decrease in labor pain intensity in the first phase active. Research Method: Quasi-experimental research type with pretest-posttest with control group design. Research carried out in the delivery room of the RB Kasih Ibu in Yogyakarta. with a population of all the first-time maternity mothers give birth at the RB Kasih Ibu in Yogyakarta. While the sample is taken with nonrandom sampling using the criteria: first pregnancy, age 20-35 years, single pregnancy, term, the first stage of labor, maternal physical condition normal. Obtained 30 treatment samples and 30 control samples. The free variable is birth ball therapy, whereas the dependent variable was the duration of the second stage and the intensity of labor pain which was measured using the observation sheet and pain scale measurement using the Universal Pain Assessment Tool. Data analysis with percentage, average, and test Chi-Square. Results: There was an effect of birth ball therapy on the second stage of labor (p-value 0.001), the average length of the second stage of labor at the treatment group was shorter (mean 21.3 minutes) than in the control group (average 36.5 minutes), mean pain intensity before treatment 6.4 and after treatment 4.9 resulting in a decrease in pain intensity (p-value 0.019), Long time ago Conclusion: There is an effect of therapy/prayer/influence on the duration of delivery and decreased intensity.